2011
DOI: 10.1007/s12205-011-1307-5
|View full text |Cite
|
Sign up to set email alerts
|

Pullout behavior of cell-type tires in reinforced soil structures

Abstract: A series of field-scaled pullout tests were carried out to investigate the pullout behavior of cell-type tires in reinforced soil structures. It is difficult to perform laboratory-scale pullout tests due to the size and geometry of the cell-type tires. Therefore it was necessary to perform field tests. The purpose of the field tests carried out in this study was to investigate the effects of surcharge height, effective anchorage length, tires connection materials, and the number of tires on the pullout behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The literature on tyre reinforcement has shown that the ultimate pull-out capacity of a waste tyre is 1.25 times that of a geocell or similar reinforcing material (Kim et al, 2011). In addition, the effect of reinforcement has also been found to be significant when applied to a sand foundation (Yoon et al, 2004(Yoon et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on tyre reinforcement has shown that the ultimate pull-out capacity of a waste tyre is 1.25 times that of a geocell or similar reinforcing material (Kim et al, 2011). In addition, the effect of reinforcement has also been found to be significant when applied to a sand foundation (Yoon et al, 2004(Yoon et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Another form of use has been as a ground reinforcement, either with the whole tires or strips [26][27][28][29][30][31]. In recent studies [30], researchers discussed the benefits of reinforcing dikes and embankments with the whole tire by running a series of field-level pullout tests to investigate the behavior of waste tire extraction in cell-type arrangements on reinforced soil.…”
Section: Introductionmentioning
confidence: 99%
“…The tire reinforcement literature has shown that the ultimate tire extraction capacity is 1.25 times that of a geo cell or similar reinforcement material [29]. The RTS system has proven to be efficient in the construction of retaining walls [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [ 18 ] have shown the benefits of reinforcing dikes and embankments with whole tires, whilst [ 19 , 20 ] found that with the addition of tire shreds, the shear strength properties of the reinforced soil were higher than the properties of the unreinforced soil. If waste tire particles are added to a clayey soil and mixed with cement, the performance of the cement admixed soil can be significantly improved [ 21 ]. They carried out a series of field-scale pull-out tests to investigate the pull-out behavior of cell-type waste tires in reinforced soil.…”
Section: Introductionmentioning
confidence: 99%